Changes to the cardiac biomarkers of non-elite athletes completing the 2009 London Marathon. Issue 5 (19th March 2013) - Baker, Polly; Davies, Sarah Louise; Larkin, Joanne; Moult, Daniel; Benton, Sally; Roberts, Andrew; Harris, Timothy
Abstract : Introduction: Many studies have demonstrated a rise in troponin and brain natriuretic peptide (BNP) levels following prolonged and/or strenuous exercise. Only one study looked at athletes who collapse and this showed no difference in cardiac biomarkers between those who collapsed and those who completed without requiring medical attention. We set out to describe and quantify the changes in troponin and BNP in three groups of non-elite runners at the 2009 London marathon: those with and without known structural heart disease (SHD) and those who collapsed on completion. Methods: The first group (recruited group, RG) was recruited at the prerace exhibition. This group had two subsets, runners with SHD and without (non-SHD). A second group was recruited from those who collapsed (collapsed group, CG). Blood was taken for troponin I (TnI), troponin T (TnT), high sensitivity TnT (HSTnT) and BNP. Results: Cardiac biomarker levels increased in all groups following the marathon. No statistically significant difference was seen between the SHD and non-SHD subgroups. When comparing the RG and CG the number and degree of rise was greater in those who collapsed. A trend for the degree of rise of HSTnT was demonstrated. Discussion: We identified runners with troponin levels that, in other circumstances, would raise concern for myocardial necrosis. However absence of adverse clinical sequelae would suggest this rise is physiological. The cause and clinical significance of the increased HSTnT levels seen in those that collapsed is yet to be fully elucidated.